English Education Students' Attitude toward Autonomous Learning Amidst the Abundant Online Learning Sources - Kurniawati, Atin (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The development of information and communication technology has provided various learning resources that can be accessed by students anytime and anywhere, including for learning languages. This should provide benefits for improving students’ language skills. This article explored several things related to the use of online learning resources by students majoring in English Education, including three problem statements, namely: (1) what kind of online learning activities did the students do for autonomous learning purposes? ; (2) what kind of improvement did they obtain from autonomous online learning activities? ; (3) what were the challenges they found in using online learning sources for autonomous learning activities? This study utilized quantitative and qualitative data to provide detailed description. Furthermore, the data was analyzed thematically. This study revealed that students tended to use social media, Youtube, and university LMS for their autonomous learning. Their reported that their autonomous learning improved their English skills, especially in listening, speaking and vocabulary mastery. It was influenced by their interest in certain skills and the learning resources they accessed. The challenges associated with online autonomous learning were unstable connections, lack of clear learning goals, and low student motivation. Several implications and recommendations are also discussed in this study.